Showing Core-Concepts of Informatics to Kids and Their Teachers - Mittermeir, Roland T.; Bischof, Ernestine; Hodnigg, Karin (Teaching Fundamental Concepts of Informatics, 2010)
Computer science education in schools focuses in many countries on the use of IT-equipment rather than on foundational concepts informatics of fers. Although this is partly justified by immediate use of IT-literacy of pupils, it is as much due to the lack of deeper knowledge in computing on the part of teachers. But this application-based instruction distorts the pupil’s percep tion of informatics and thus, leads to lack of interest in informatics related professions. This paper reports on a project that shows both, pupils and teachers, some principles of informatics in order to make the students curious to learn more about it and showing both groups that informatics offers more than its applications. It also shows teachers that concepts of informatics are not too difficult to teach and to grasp.